Assessment of relapse of skeletal open bite treatment in adult patients treated with molar intrusion using temporary anchorage devices and orthognathic surgery - a systematic review - Jnaneshwar, Poornima; Devasagayam, Davis; Rajaram, Krishnaraj; Venkatesan, Keerthi; Sampath, Arvind; Thandapani, Anandhita; Haridas, Arvind (Brazilian Dental Science, 2022)
Objective: The purpose of this study is to systematically assess the available evidence for relapse of skeletalopen bite treatment using temporary anchorage devices and orthognathic surgery. Materials and Methods: Fiveelectronic databases such as MEDLINE, COCHRANE, SCIELO, GOOGLE SCHOLAR, EMBASE were systematicallysearched up to June 2020. Methodological quality studies were graded by means of the Effective Public HealthPractice Project (EPHPP) Quality Assessment Tool. Results: In total, 1005 studies were identified for screening,and 6 studies were eligible. The quality assessment tool showed moderate quality for all the studies. Theimmediate post treatment correction of open bite was better in the surgical studies than in the studies treatedwith TADs. Conclusion: Stability of treatment results of anterior openbite was comparable in cases treated inboth the treatment modalities. Relapse of anterior open bite was associated with cases in which the posttreatmentoverbite was minimal. Overbite seems to be more stable when only the maxilla has been operated on than withbi-maxillary surgeries. Counterclockwise rotation of the mandible with subsequent reduction of anterior facialheight was better in surgical correction than through TADs.KEYWORDSSkeletal open bite; Temporary anchorage devices; LeFort 1 impaction; Bi-maxillary surgery.